ANALISIS PELAKSANAAN PRAKTIKUM BIOLOGI DAN UPAYA MENINGKATKAN PEMAHAMAN KONSEP DAN PENALARAN MATEMATIKA DENGAN MENGGUNAKAN MODEL PEMBELAJARAN BERBASIS MASALAH DI SMA NEGERI 2 BINJAI - Efendi, M Yus; Armanto, Dian; Asmin, Asmin (TABULARASA, 2013)
This Classroom Action Research (CAR) aims to find out: how the effectiveness and students response to the problem based learning model in improving the understanding of mathematical concepts and reasoning of students SMA Negeri 2 Binjai. This CAR was conducted in two cycles with stages of planning, action, observation and reflection. The method used to apply a model of problem-based learning during the learning processing class. The instrument was used the end of each test cycle I and II, teacher observation sheet, student observation sheets and student questionnaire responses to the implementation f problem based learning. From 32 students there are 28 students (87.50%) stated that students complete individually who scored â¥ 76 with an average of 80.56. Value of the class average is 79.25 with the level of exhaustiveness learn classical is planned minimum is 85%. Effectiveness of problem-based learning modelis designed to form small study groups consisting of 5-6 people is very good and effective in improving the understanding of mathematical concepts and reasoning. 87% of students responded positively and fun to the learning process, 91% of students claimed to give them the opportunity to think and 84% found it easier to understand mathematical concepts and develop reasoning through a problem-based learning.